(The poetic grammatical reference and its role in the lexical dictionary - Descriptive Analytical Study in (Mokhtar Al Sahah - Ieqilan, Abdul Karim Abdul Qadir (Journal of Humanities & Social Sciences, 2019)
The aim of this paper is to highlight the poetic reference from a linguistic viewpoint, and to describe the way linguists have used poetic references in dictionaries using a certain dictionary ( Mokhtar Al Sahah) as a model.The research has therefore presented some models based on the above mentioned model showing the method which Al Razi used to describe places of reference and its relation to the translated lexical terms used , taking into account other linguists view on the reference matter.An analytical view is then presented for various aspects of poetic referencing in dictionaries, such as the relation between referencing and the subject matter in the dictionary and its importance.The research has come to several conclusions which have unveiled that Al Razi has used linguistic poetic referencing when translating lexical terms following in the footsteps of his predecessors in this area, and realizing the importance of linguistic poetic referencing in reinforcing the functions of dictionaries which needs pointers for meaning and lexical organizing to the best linguistic levels.He has also realized that there are some pointers which are inhibited by pronunciation and is not shown except through linguistic compounding which is used as a link for lexical terms.The paper also highlights the importance of linguistic poetic referencing which distinguishes the proper usage of lexicons in both prose and poetry.
Keywords: the grammatical witness; the home of the witness; the poetic necessity; the lexicon; the semantics